Desain Logo Kemasan Bagi Umkm Desa Oluhuta Sebagai Langkah Awal Media Promosi Kreatif - Lukman Pakaya; Ayu Rakhma Wuryandini (Lembaga Pengembangan Kinerja Dosen, 2023)
Oluhuta Village, including villages in the Tomini Bay area. Oluhuta village is the eighth village of nine villages in the Kabila Bone sub-district, Bone Bolango district, Gorontalo province. Servants bring the KKN MBKM program as a form of the tri dharma of Higher Education to educate the nation's life. The problem faced by the village of Oluhuta is that MSMEs in Oluhuta Village still have deficiencies in designing the packaging logo for the products they produce, namely skipjack tuna, so they are less attractive to buyers for transactions. The methods used in this community service program are 1) location observation surveys, 2) interviews, 3) coaching. The results of the dedication to the Oluhuta village community Helping creative, innovative and more modern Oluhuta villagers who become entrepreneurs to improve the economy of the village community, especially MSME actors